2020
DOI: 10.1002/cbic.201900661
|View full text |Cite
|
Sign up to set email alerts
|

Azido‐Desferrioxamine Siderophores as Functional Click‐Chemistry Probes Generated in Culture upon Adding a Diazo‐Transfer Reagent

Abstract: Scheme1.Structures of DFOB (1), azido-DFOB( 2), DFON 1 ,DFOA 1-3 ,a nd membersoffour classes of PDB substrates used to augment culturesofS. pilosus. ( 1), together with its observed MS 2 fragmentationpattern, B) DFOA-constitutional isomers 3-9,g enerated by usingP DB with DB as substrate, and the corresponding azido analogues 10-16,a nd C) putative dimeric and monomeric compounds that could be generated by using PDB with 5APAa ssubstrate. Scheme2.Structures of:A)DFOB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…46 Interestingly, researchers have also found that under putrescine-depleted conditions, Shewanella putrefaciens shifts to producing desferrioxamine B when cadaverine precursors are available. 47 In desferrioxamine biosynthesis, incorporation of the putrescine precursor in desferrioxamine A1 has been shown before in multiple species 30,44,48 and now in this study with the discovery of legonoxamine G.…”
Section: Molecular Networking and Ms/ms Based Structure Elucidationsupporting
confidence: 65%
See 1 more Smart Citation
“…46 Interestingly, researchers have also found that under putrescine-depleted conditions, Shewanella putrefaciens shifts to producing desferrioxamine B when cadaverine precursors are available. 47 In desferrioxamine biosynthesis, incorporation of the putrescine precursor in desferrioxamine A1 has been shown before in multiple species 30,44,48 and now in this study with the discovery of legonoxamine G.…”
Section: Molecular Networking and Ms/ms Based Structure Elucidationsupporting
confidence: 65%
“…Legonoxamine F contains one 1,6-diaminohexane instead of cxthe typical 1,5-diaminopentane. This is a well-established phenomenon in siderophore biosynthesis 31,44 linking it to the promiscuity of the S29 des biosynthetic gene cluster. Legonoxamine G contains a N-hydroxyputrescine moiety due to the initial loss of 104 Da instead of the typical 118 Da associated to N-hydroxycadaverine.…”
Section: Molecular Networking and Ms/ms Based Structure Elucidationmentioning
confidence: 98%
“…Legonoxamine F contains one 1,6-diaminohexane instead of the typical 1,5diaminopentane. This is a well-established phenomenon in siderophore biosynthesis 31,44 linking it to the promiscuity of the S29 des biosynthetic gene cluster. Legonoxamine G contains a N-hydroxyputrescine moiety due to the initial loss of 104 Da instead of the typical 118 Da associated to N-hydroxycadaverine.…”
Section: Streptomyces Sp S29 Cocultivation and Lc-ms Of Desferrioxammentioning
confidence: 98%
“…Such conjugates can be further used as drugs to treat infections with pathogenic bacteria. More recently, the team attempted to incorporate azido amine substates but failed to produce azido DFOB analogs [ 70 ], suggesting that although the biosynthetic enzymes are somewhat permissive, not any substrate can be tolerated.…”
Section: Precursor-directed Biosynthesismentioning
confidence: 99%